The Performance of the Nigerian Manufacturing Sector: A 52-Year Analysis of Growth and Retrogression (1960-2012) - Banjoko, Simbo A; I. I, Iwuji; K, Bagshaw (Journal of Asian Business Strategy, 2012)
This paper examines the performance of the Nigerian manufacturing sector since independence in 1960 using such performance indices as percentage contribution to the Gross Domestic Product, index of manufactured products, percentage growth rate, manufacturing value added, employment growth rate, and percentage of capacity utilization within this period. Secondary sources like the Central Bank of Nigeria Statistical Bulletin, Annual Reports and Statements of Accounts as well as the Statistical Facts sheets of the National Bureau of Statistics and other publications were used in collecting the data. The main finding is that despite many policies and developmental initiatives undertaken by successive civilian and military administrations since independence, the Nigerian manufacturing sector has grossly underperformed in relation to its potentials. Daunting challenges facing the sector include unfavourable business environment, erratic power supply, poor and decaying physical infrastructures, multiple taxations, obsolete technology, high interest rates and inconsistency in government policies. The paper concludes by making recommendations for achieving a verile manufacturing sector.